Evaluation of a novel procedure for rapid detection of carbapenemase-producing Enterobacteriaceae (CPE) using the LightMix® modular carbapenemase kits. (26th August 2016) - Oviaño, Marina; Torres, Isabel; González, Maria; Bou, Germán
Abstract : Objectives: Evaluation of the LightMix ® modular carbapenemase kits for the rapid detection of carbapenemase-producing Enterobacteriaceae (CPE) and the application of these kits to the direct detection of colonized patients and bacteraemias. Methods: The modular multiplex PCR kits targeting bla KPC, bla NDM, bla VIM, bla IMP and bla OXA-48 -like carbapenem resistance genes were evaluated in terms of sensitivity and specificity for carbapenemase resistance in a set of 118 labelled clinical isolates. Among these, 96 were CPE genotypically characterized by PCR and sequencing. The limits of detection were calculated for the different carbapenem resistance genes in terms of cfu/mL. In addition, the kits were used to evaluate colonization of patients by CPE by comparing this assay with the Xpert ® Carba-R Kit on 127 rectal, perirectal and pharyngeal samples. Blood cultures from bacteraemias (4) and spiked blood cultures (23) with genotypically characterized isolates were also evaluated. Results: The overall sensitivity and specificity of the multiplex PCR assay was 99% and 100%, respectively. The limit of detection for bla KPC, bla VIM, bla IMP and bla OXA-48 -like is 60 cfu/mL and for bla NDM 500 cfu/mL. The colonization and bacteraemia studies revealed a 100% agreement between the results obtained by this assay and the ones obtained by GeneXpert ® . Conclusions: The LightMix ® modular carbapenemase kits are highly reliable and utilizable assays for both colonized and septic patients, and can help in the improvement of infection control. Their modular design facilitates cost-effective detection of CPE in hospital settings.